Fighting African capital flight: Trajectories, dynamics and tendencies - Simplice Asongu; Joseph I. Uduji; Elda N. Okolo-Obasi (African Governance and Development Institute (AGDI), 2019)
An April 2015 World Bank report on attainment of the Millennium Development Goal (MDG) extreme poverty target has revealed that extreme poverty has been decreasing in all regions of the world with the exception of sub-Saharan Africa (SSA), in spite of the sub-region enjoying more than two decades of growth resurgence. This study builds on a critique of Piketty's 'capital in the 21st century' and recent methodological innovations on reverse Solow-Swan to review empirics on the adoption of common policy initiatives against a cause of extreme poverty in SSA: capital flight. The richness of the dataset enables the derivation of 14 fundamental characteristics of African capital flight based on income-levels, legal origins, natural resources, political stability, regional proximity and religious domination. The main finding reveals that regardless of fundamental characteristic, from a projection date of 2010, a genuine timeframe for harmonizing policies is between 2016 and 2023. In other words, the beginning of the post-2015 agenda on sustainable development goals coincides with the timeframe for common capital flight policies.
Keywords: C50; E62; F34; O19; O55; 330; Econometric modeling; Capital flight; Poverty; Africa